2017
DOI: 10.4236/jmf.2017.71007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Exchange Rate Volatility: Application of the GARCH and EGARCH Models

Abstract: Policy makers need accurate forecasts about future values of exchange rates. This is due to the fact that exchange rate volatility is a useful measure of uncertainty about the economic environment of a country. This paper applies univariate nonlinear time series analysis to the daily (TZS/USD) exchange rate data spanning from January 4, 2009 to July 27, 2015 to examine the behavior of exchange rate in Tanzania. To capture the symmetry effect in exchange rate data, the paper applies both ARCH and GARCH models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 40 publications
2
32
0
3
Order By: Relevance
“…Recent studies confirmed that the GARCH(1,1) model is the most appropriate measure of exchange-rate volatility [34,35]. Additionally, research by [36] revealed that the exchange-rate series exhibits empirical regularities such as clustering volatility, non-stationarity, non-normality, and serial correlation, which justify the application of the GARCH methodology. Another recent study by [37] that used GARCH(1,1) found that exchange rate volatility affects both international trade and foreign direct investment (FDI) significantly but negatively in countries engaged in OBOR (One Belt One Road is a global development strategy adopted by the Chinese government involving infrastructure development and investments in 152 countries and international organizations in Asia, Europe, Africa, the Middle East, and the Americas).…”
Section: Methodsologymentioning
confidence: 96%
“…Recent studies confirmed that the GARCH(1,1) model is the most appropriate measure of exchange-rate volatility [34,35]. Additionally, research by [36] revealed that the exchange-rate series exhibits empirical regularities such as clustering volatility, non-stationarity, non-normality, and serial correlation, which justify the application of the GARCH methodology. Another recent study by [37] that used GARCH(1,1) found that exchange rate volatility affects both international trade and foreign direct investment (FDI) significantly but negatively in countries engaged in OBOR (One Belt One Road is a global development strategy adopted by the Chinese government involving infrastructure development and investments in 152 countries and international organizations in Asia, Europe, Africa, the Middle East, and the Americas).…”
Section: Methodsologymentioning
confidence: 96%
“…Ayrıca bu çalışmalar, döviz kurundaki değişimin oynaklık kümelenmesi (volatility clustering) sergilediğini yani kur getirilerinde meydana gelen büyük değişimleri büyük, küçük değişimleri ise yine küçük miktarlı değişimlerin izlediğini ortaya koymaktadır. Finansal piyasaların hareketli bir enstrümanı olan döviz kurlarının bu dinamik yapısının anlaşılması ve zaman içerisinde değişkenlik gösteren volatilitesinin modellenmesine yönelik birçok çalışma yapılmıştır (Hsieh, 1988;McKenzie ve Mitchell, 2002;Beine ve diğerleri, 2003;Mapa 2004;Sandoval, 2006;Vee ve diğerleri, 2011;Antonakakis ve Darby, 2013;Miletić, 2015;Epaphra, 2017;Stillwagon ve Sullivan, 2019).…”
Section: Li̇teratür Taramasiunclassified
“…The study found that negative shocks had a larger impact than the positive shocks in the market under the study. Univariate nonlinear time series analysis was applied by [13] to the daily (TZS/USD) exchange rate data spanning from January 4, 2009 to July 27, 2015 to examine the behavior of the exchange rate in Tanzania. Both ARCH and GARCH models were used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mean Absolute Error (MAE) has also been calculated to evaluate the efficacy of forecasting. Both these measures have been used by many previous studies including [6] and [13] amongst others. Thereafter, the Diebold-Mariano [14] test, henceforth DM, is used to compare the predictive accuracy of both the models over the entire sample period.…”
Section: Introductionmentioning
confidence: 99%